The relation of Social Contradiction Theory with Arrestees' Use of Cocaine and Opiates - Mohammad Mahdi Faturehchi (Drug Control Headquarters, Research and Education Office, 2004)
The present research applies the information of major plans for predicting drug consumption in 1991/1992 as well as the data of census in 1990 to evaluate this assumption that " some arrestees' sturctural weakness-related factors" contribute in using cocaine and other opiates. This research which applies non-linear modelling techniques، reviews the effectivity of the social control factors as well as population factors in foresighting the rate of drug consumption among arrestees. This issue is also evalauted wether there is any change in the effects of such factors in the rate of drug consumption despite of structural weakness of arrestees' residential areas. In general، the research concludes that there should be a relationship between a group of major drug users and the structural weakness of environmental factors.